Dose of furosemide before admission predicts diuretic efficiency and long‐term prognosis in acute heart failure. (11th November 2021) - Blázquez‐Bermejo, Zorba; Farré, Nuria; Caravaca Perez, Pedro; Llagostera, Marc; Morán‐Fernández, Laura; Fort, Aleix; de Juan Bagudá, Javier; García‐Cosio, María Dolores; Ruiz‐Bustillo, Sonia; Delgado, Juan F.
Abstract: Aims: The outpatient diuretic dose is a marker of diuretic resistance and prognosis in chronic heart failure (HF). Still, the impact of the preadmission dose on diuretic efficiency (DE) and prognosis in acute HF is not fully known. Methods and results: We conducted an observational and prospective study. All patients admitted for acute HF treated with intravenous diuretic and at least one criterion of congestion on admission were evaluated. Decongestion [physical examination, hemoconcentration, N‐terminal pro‐brain natriuretic peptide (NT‐proBNP) change, and lung ultrasound], DE (weight loss and urine output per unit of 40 mg furosemide), and urinary sodium were monitored on the fifth day of admission. DE was dichotomized into high–low based on the median value. A multivariate Cox regression analysis was conducted to find predictors of HF readmission or mortality. A total of 105 patients were included between July 2017 and July 2019. Mean age was 74.5 ± 12.0 years, 64.8% were male, 33.3% had de novo HF, and mean left ventricular ejection fraction was 46 ± 17%. Median follow‐up was 26 [15–35] months. Low DE based on weight loss was associated with a higher previous dose of furosemide (odds ratio [OR] 1.01 [1.00–1.02]), thiazide treatment before admission (OR 9.37 [2.19–40.14]), and lower diastolic blood pressure (OR 0.95 [0.91–0.98]) in the multivariate regression model. Only previous dose of furosemide (OR 1.01 [1.00–1.02]) and haemoglobin at admission (OR 0.76 [0.58–0.99]) were associated with low DE based on urine output in the multivariate analysis. The correlation between the previous dose of furosemide and DE based on weight loss was poor ( r = −0.12; P = 0.209) and with DE based on urine output was weak to moderate ( r = −0.33; P < 0.001). Low DE based on weight loss and urine output was associated with lesser decongestion measured by NT‐proBNP ( P = 0.011; P = 0.007), hemoconcentration ( P = 0.006; P = 0.044), and lung ultrasound ( P = 0.034; P = 0.029), but not by physical examination ( P = 0.506; P = 0.560). Survival and event‐free survival in acute decompensated HF (ADHF) were lower than in de novo HF; a preadmission dose of furosemide > 80 mg in ADHF identified patients with particularly poor prognosis (log‐rank < 0.001). In ADHF, the preadmission dose of furosemide (hazard ratio [HR] 1.34 [1.08–1.67] per 40 mg) and NT‐proBNP at admission (HR 1.03 [1.01–1.06] per 1000 pg/mL) were independently associated with mortality or HF readmission in the multivariate Cox regression analysis. Conclusions: The outpatient dose of furosemide before acute HF admission predicts DE and must be taken into account when deciding on the initial diuretic dose. In ADHF, the outpatient dose of furosemide can predict long‐term prognosis better than DE during hospitalization.